Effective Inventory Management of Entrepreneurs in Eastern Part Thailand: 10 Big Questions - Suvittawat, Adisak (Information Management and Business Review, 2015)
The objective of this research is finding the variables which effect on entrepreneurs’ inventory management in eastern part of Thailand. The entrepreneurs have been identified in 2 difference sizes, large and small as the inventory management variables must be different. The results show that inventory management of large size were accepted by the entrepreneurs are space utilization, product sample, product feature differentiation, effective inventory management system, inventory management objective, effective inventory picking system, inventory cost reduction, regular problem happen, effective IT system and specific soft ware for inventory management. The results show that inventory management of small size were accepted by the entrepreneurs are specific soft ware for inventory management, effective IT system, inventory management objective, effective inventory picking system, regular problem happen, product feature differentiation, inventory cost reduction, product sample, space utilization and effective inventory management. Inventory management in small firm and big firm has significantly priorities as the big firms have advantage in space utilization but need specific soft ware for inventory management due to big firms have more products or inventories items than small firms.